Pembiayaan Perusahaan Melalui Factoring: Solusi Alternatif Untuk Mengelola Arus Kas Dan Likuiditas - Amini, Risya Ainun Zakiyah; Mulyati, Etty (Peneliti.net, 2025)
Factoring is an alternative form of financing that is increasingly popular among companies, especially SMEs, as a solution to accelerate cash flow. Through factoring, companies can sell their receivables to third parties (factoring) to get cash immediately, without having to wait for payment due from customers. This article discusses the mechanism of factoring, the types of factoring, the benefits and risks involved, and how factoring can be a strategic instrument in managing a company's liquidity. This study also looks at case studies of the application of factoring in small and medium-sized companies as a solution to increase financial flexibility